On Congruent Econometric Relations: A Comment. - Hendry, D (Elsevier, 1997)
The paper responds to the claimed criticisms in Faust and Whiteman (1997) of the ‘LSE’ approach to empirical macro-econometrics. Their bold attempt to inter-relate ‘alternative methodologies’ is undone by misconceptions which lead them to incorrect conclusions. To clarify the analysis, the notion of structure is reviewed to underpin sustainable econometric relations, then identification and exogeneity are reconsidered. The theory of reduction and modelling strategies are examined, as is the basis for policy. The results rebut their claims, and confirm the need for a progressive research strategy which combines the best of both theory and evidence.